History of the Armenians in India - Seth, Mesrovb Jacob (My University, 2004)
The only history of its kind ever written, this book narrates the advent of the Armenian colony in India and its contribution to the East India Company. Seth describes in detail the Armenians' commerce and power, as well as their literary and social activities
By Mesrovb J. Seth. - Piscataway : Gorgias Press, 2004. - xxii, 190 p. ; 23 cm. - Includes bibliographical reference
Տվյալները՝ ինտերնետային կայքից
https://dokumen.pub/qdownload/history-of-the-armenians-in-india-9781463208615.html
Keywords: Armenians-India-History; India-History